KAJIAN TRANSFORMASI GELOMBANG STUDI KASUS PPI CISOLOK DENGAN MODEL CG WAVE - Novi Andhi Setyo Purwono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2006)
AbstractTo support the solving of hydrodynamics coastal, estuari or port teritorial problem especially wave propagation, the mathemathical model represent one of the solution which often used. Simulation model is useful in development and planning at coastal area, so that impact which possible happened can anticipate early . mathemathical model which is used in this research is SMS BOSS, CGWAVE. Any data which needed in research is cover layout,Â  bathymetry and occurence waving. In this research will study about occurence waving in study area with daily wave and plan wave with various incident wave direction. Result of simulation model showing that with daily wave and wave plan from south is highest compared with other incident wave direction. Wave high of daily at port pool is 0.36 until 1.38 m, at port mouth 2.08 m and at territorial water 0.87 until 1.98 m. Wave high of wave plan that happened at port pool is 0.43 - 1.37 m, at port mouth 2.21 m and at territorial water 1.19 - 4.59 m.Â Key word: CG WAVE